Human pegivirus‐1 associated leukoencephalitis: Clinical and molecular features. Issue 5 (8th November 2018) - Balcom, Erin F.; Doan, Matthew A.L.; Branton, William G.; Jovel, Juan; Blevins, Gregg; Edguer, Beste; Hobman, Tom C.; Yacyshyn, Elaine; Emery, Derek; Box, Adrian; van Landeghem, Frank K.H.; Power, Christopher
Abstract : Etiologic diagnosis is uncertain in 35% to 50% of patients with encephalitis, despite its substantial global prevalence and disease burden. We report on 2 adult female patients with fatal leukoencephalitis associated with human pegivirus‐1 (HPgV‐1) brain infection. Neuroimaging showed inflammatory changes in cerebral white matter. Brain‐derived HPgV‐1 RNA sequences clustered phylogenetically with other pegiviruses despite an 87‐nucleotide deletion in the viral nonstructural (NS)2 gene. Neuropathology disclosed lymphocyte infiltration and gliosis predominantly in brain white matter. HPgV‐1 NS5A antigen was detected in lymphocytes as well as in astrocytes and oligodendrocytes. HPgV‐1 neuroadaptation should be considered in the differential diagnosis of progressive leukoencephalitis in humans. Ann Neurol 2018;84:789–795